2014
DOI: 10.3390/ijms15057865
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Alzheimer’s Disease Analysis by Mass Spectrometry-Based Proteomics

Abstract: Alzheimer’s disease (AD) is a common chronic and destructive disease. The early diagnosis of AD is difficult, thus the need for clinically applicable biomarkers development is growing rapidly. There are many methods to biomarker discovery and identification. In this review, we aim to summarize Mass spectrometry (MS)-based proteomics studies on AD and discuss thoroughly the methods to identify candidate biomarkers in cerebrospinal fluid (CSF) and blood. This review will also discuss the potential research areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 131 publications
0
30
0
Order By: Relevance
“…[18][19] There are suggestive evidences that changes in plasma or serum Aβ 40 , Aβ 42 , or the ratio of Aβ 42 /Aβ 40 may be associated with individuals at risk for developing AD. [20][21] Some studies, comparing clinically diagnosed AD patients with normal elderly individuals, showed no differences in either plasma Aβ 40 or Aβ 42 .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19] There are suggestive evidences that changes in plasma or serum Aβ 40 , Aβ 42 , or the ratio of Aβ 42 /Aβ 40 may be associated with individuals at risk for developing AD. [20][21] Some studies, comparing clinically diagnosed AD patients with normal elderly individuals, showed no differences in either plasma Aβ 40 or Aβ 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Tau CSF levels have been measured with conventional methods such as enzyme-linked immunosorbent assay (ELISA), mass spectrometry or surface plasmon resonance, which are timeconsuming and/or expensive (Hye et al, 2014;Liu et al, 2014;Mehta et al, 2000;Sparks et al, 2012;Tuantranont, 2013). Researchers have made great efforts to generate rapid, cost-effective and highly sensitive detection tests using biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Other than blood, cerebrospinal fluid (CSF), which directly interacts with the space of the brain and reflects biochemical changes that occurs in the brain, has also been used for the biomarker of dementia and AD. Proteins such as phospholipases A2, visinin-like 1, microtubule-associated protein tau, neurofilament proteins, and many more that were reviewed by Liu et al [70] have been considered as CSF biomarkers of AD. The increase in the generation of 2,4-dihydroxybutyrate with the progression of MCI was noted and considered as a promising biomarker of AD [51,71].…”
Section: Proteomic Biomarkers Of Dementiamentioning
confidence: 99%
“…Mass spectrometry-based proteomics has been widely used for biomarkers of dementia and AD [64]. Proteins such as Aβ40, Aβ42, and their ratio Aβ42:Aβ40 have been linked with AD and dementia [65].…”
Section: Proteomic Biomarkers Of Dementiamentioning
confidence: 99%